STUDI EKSPERIMEN KUAT TEKAN, KUAT TARIK BELAH DAN MODULUS ELASTISITAS UNTUK BETON NORMAL DENGAN TAMBAHAN VARIASI FILLER - Permana, Dian; Mungok, Chrisna Djaja; Handalan, Cek Putera (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
This paper presents the influence of the use of filler (rock dust) against the normal concrete cement Portland Composite Cement (PCC) brand Holcim, test specimens made cylindrical with size Ø 15 cm height 30 cm. Determination of concrete mixture using ACI Modification method, The planned concrete quality is fc '= 25 MPa. The result of compressive strength is 41,05 Mpa, for concrete mox 15% yield of 37,27 Mpa compressive strength, 25% concrete mix concrete result 33,12 Mpa, while for concrete mix 35% result 31,71 Mpa. There is a considerable difference in the range of results obtained, this is because the gradations are not uniform, abrasion ? 40% and the difference in slump value. Keywords: Compressive strength, Split Tensile Strength, PCC cement.